Voluntary Pension Saving in Chile and Latin America (GESTIÓN Y TENDENCIAS, 2020)
Voluntary pension saving has become an important pillar of pension systems because it improves the coverage and adequacy of pensions, increasing their long-term sustainability. The growing need for resources to fund future pensions is particularly relevant given population aging, high rates of informality, the decline in expected returns on financial assets, and mounting pressure to access pension funds before retirement. The articles in this special issue provide a broad analysis that benefits from the joint work of academics, regulators, and international bodies such as the IDB.
Keywords: pension saving; editorial; UAH